2007
DOI: 10.1142/s0129183107011728
|View full text |Cite
|
Sign up to set email alerts
|

Clusterization, Frustration and Collectivity in Random Networks

Abstract: We consider the random Erdős-Rényi network with enhanced clusterization and Ising spins s = ±1 at the network nodes. Mutually linked spins interact with energy J. Magnetic properties of the system as dependent on the clustering coefficient C are investigated with the Monte Carlo heat bath algorithm. For J > 0 the Curie temperature Tc increases from 3.9 to 5.5 when C increases from almost zero to 0.18. These results deviate only slightly from the mean field theory. For J < 0 the spin-glass phase appears below T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
3
1
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 32 publications
2
14
0
Order By: Relevance
“…This limit value can be lower, if G → L(G) is applied to selected local subnetworks and not to the whole system. The density of the transformed nodes can be used to tune C, similarly to [11,12,13,14,15,16]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This limit value can be lower, if G → L(G) is applied to selected local subnetworks and not to the whole system. The density of the transformed nodes can be used to tune C, similarly to [11,12,13,14,15,16]. …”
Section: Discussionmentioning
confidence: 99%
“…The idea is to enhance C gradually by linking nodes which are neighbours of the same node. When a node has three neighbours, it is convenient to replace it by a triangle [16]; the trick is similar to the star-triangle or star-delta transformation. The latter has been used also to construct Apollonian networks with a high values of the clustering coefficient [17], and to prove some theorems in the theory of percolation [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter networks are prepared from the usual Erdös-R'enyi network by adding some links between neighbors of the same nodes. The procedure, applied by Holme and Kim to the scale-free networks [35], was adapted later [36] to the Erdös-R'enyi networks. As a rule, the modified networks contained 10 3 nodes, with mean degree < k >= 10.00 ± 0.5.…”
Section: The Modelmentioning
confidence: 99%
“…In our former texts, we calculated the transition temperature T SG of the Erdös-Rényi networks [10] and of the regular network [11]. The results indicated that on the contrary to the anticipations of the Bethe theory T SG decreases with the clustering coefficient C. However, in both cases we dealt with the networks endowed with the small-world property.…”
Section: Introductionmentioning
confidence: 99%